BODY MASS INDEX STATUS WITH HYPERTENSION - Tri hardi Miftahul Ulum; Liza Novitasari Wijaya (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Hypertension is the leading cause of premature death in the world. It does not only attack the productive age but also attacks the elderly. Hypertension is known as